Scientific computing : an introduction with parallel computing - Golub, Gene H. (Gene Howard), 1932-2007; Ortega, James M., 1932- (Academic Press, Inc., 1993)
This book introduces the basic concepts of parallel and vector computing in the context of an introduction to numerical methods. It contains chapters on parallel and vector matrix multiplication and solution of linear systems by direct and iterative methods. It is suitable for advanced undergraduate and beginning graduate courses in computer science, applied mathematics, and engineering. Ideally, students will have access to a parallel or Vector computer, but the material can be studied profitably in any case.